1978
DOI: 10.1115/1.3426202
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Machining of Bone

Abstract: An investigation is described of the mechanics of orthogonal machining of bone. Experimental results are presented for the machining forces and specific energies for various cutting orientations, rake angles, and depths of cut. From microscopic observations on sections taken through the cutting zone, the chip formation process is seen to occur by a series of discrete fractures. A simple model is proposed to qualitatively describe the mechanics of chip formation. The energy expended by the cutting process under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Wiggins [5] Liao et al [11] used literature fracture toughness value to determine the cutting depth at which the transition of chip formation changes. If this method is reversed, the fracture toughness can be determined at the cutting depth but it has to be exactly known at which depth the bone chips fracture for the first time along the shear plane.…”
Section: Fracture Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiggins [5] Liao et al [11] used literature fracture toughness value to determine the cutting depth at which the transition of chip formation changes. If this method is reversed, the fracture toughness can be determined at the cutting depth but it has to be exactly known at which depth the bone chips fracture for the first time along the shear plane.…”
Section: Fracture Toughnessmentioning
confidence: 99%
“…[3] Additionally, the necessary emissivity constant of cortical bone has been formerly determined. [4] Wiggins and Malkin [5] as well as Jacobs [6] were the first to investigate the cutting forces of orthogonal cutting of cortical bone with respect to the osteonal cutting direction, tool rake angle and cutting depth. They found a non-linear relationship between cutting depth and cutting forces as well as a strong dependency of cutting direction on cutting forces, in relation to the bone micro-structure.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the test parameters used in the literature was performed, as seen in Table . It is clear that the cutting speeds utilized in the majority of the literature are far lower than that used in the recent study by Kianmajd et al ., and likewise the chip thicknesses were much larger. In fact, the current parameters used in surgery are even more extreme, with a cutting speed of 26 180 mm/s and chip thickness of 0.94–2.81 μm.…”
Section: Introductionmentioning
confidence: 59%
“…Researchers worked to establish how bone is cut during orthogonal machining. Experiments were performed on both bovine and human bone samples, and compared cutting force and specific cutting energy to the tool geometry, depth of cut, and cutting mode (the orientation of the cutting edge relative to the bone microstructure) . Both studies found that high‐rake tools (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation